Levodopa-Carbidopa Intestinal Gel in Parkinson's Disease: A Systematic Review and Meta-Analysis - Wang, Libo; Li, Jia; Chen, Jiajun (Frontiers in Neurology, 2018)
Background: Levodopa has been widely used and regarded as the most effective therapy for Parkinson’s disease (PD), but long-term treatment with oral levodopa may result in motor fluctuations and involuntary movements (dyskinesias). There is evidence to suggest that Continuous infusion of levodopa-carbidopa intestinal gel (LCIG) can effectively manage motor and non-motor complications in PD, but clinical studies investigating this have yielded inconsistent results. This systematic review and meta-analysis was performed to examine the efficacy and safety of LCIG for patients with PD. Methods: A systematic search was conducted to retrieve published data in the EMBASE, PubMed, and the Cochrane Library up to March 2018. Both efficiency and safety of LCIG were analyzed using pooled standardized mean differences (SMDs) or odds ratio (ORs) with 95% confidence interval (CIs). Results: Eight trials with 384 PD patients were included in the present study. Compared with the control group, LCIG significantly decreased off-time (SMD, -1.19; 95% CI, -2.25 to -0.12; p = 0.003) and increased on-time without troublesome dyskinesia (SMD, 0.55; 95% CI, 0.20 to 0.90; p = 0.002). However, no significant difference of LCIG was found in on-time with troublesome dyskinesia. There were no significant differences in UPDRS, Hoehn & Yahr and PDQ-39 scores. Besides, no significant differences in the drop-out and adverse effects. Conclusions: Continuous delivery of LCIG may offer a promising option for PD patients. More randomized double-blind controlled studies with large sample sizes were needed to further confirm the efficacy and safety of LCIG for PD patients.